Scientific racism in modern South Africa - Dubow, Saul 1959- (Cambridge Univ. Press, 1995)
This book is the first full-length study of the history of intellectual and scientific racism in modern South Africa. Ranging broadly across disciplines in the social sciences, sciences and humanities, it charts the rise of scientific racism and biological determinism from the late nineteenth century until the middle of the twentieth. Set against the rise of apartheid, the book illuminates the complex relationship between theories of essential racial difference and the development of white supremacist thinking. Saul Dubow draws extensively on comparable studies of intellectual racism in Europe and the United States to demonstrate the selective absorption of widely prevalent conceptions of racial difference in the particular historical context of South Africa. The issues he addresses are of relevance to both Africanist and international students of racism and race relations.